ENSINO DE BOTÂNICA EM ESPAÇOS NÃO FORMAIS DE EDUCAÇÃO NA GRANDE VITÓRIA-ES: UMA PROPOSTA DE GUIA ILUSTRADO COMO POTENCIALIZADORA DA PRÁXIS DOCENTE - Junger, Ana Paula Fantecelle (2020)
Teaching in Brazil is still very focused on a traditional approach, which ends up generating disinterest and demotivation in students. Within the subject Biology, the content that suffers the most from this is Botany, overlooked by students and teachers,